مفهوم المأساة من وجهة نظر النقد الحديث: ملامح البطل الشكسبيري في مسرحية ميللر "موت بائع" - طـه, أحمـد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to make an overall discussion of Miller's concept of the tragic hero, from a modern criticism's point of view. It also attempts to highlight his critical stance in the light of modern criticism suggesting that "the common man is as apt a subject for tragedy in its highest sense as kings were", as both fall victims for their societies, or for certain external circumstances beyond their reach, or for both. The study draws a comprehensive comparison and contrast between the traditional tragic hero in Shakespeare's plays, including Hamlet, King Lear and Macbeth, and Miller's tragic hero in his Death of a Salesman. The study comes to the conclusion that the similarities between the two cases override the differences. Moreover, the study concludes that the tragedy of the common man in Miller's plays, according to the point of view of modern criticism, holds the same social and tragic stature in the minds of the audience and stands on equal footing with the Shakespearean or Greek tragic heroes. يعالج البحث مفهوم ميللر للبطل التراجيدي من وجهة نظر النقد الحديث؛ يُسلط البحث الضوء على هذا المفهوم من خلا ل وجهة نظر النقد الحديث الذي يعتبر أن الإنسان العادي يمكن أن يكون موضوعا لقصة تراجيدية بكل ما تحويه الكلمة من معنى ، كما كانت الحال بالنسبة للملوك، وذلك لكون كلتا الشخصيتين ضحية لمجتمعها، أو لظروف معينة خارجة عن إرادتها، أو لكلتا الحالتين معاً. يجري البحث مقارنة شاملة بين مفهوم البطل التراجيدي الأرسطي، ذلك المفهوم الذي تبناه شكسبير في معظم مسرحياته، بما في ذلك "هاملت"، و"الملك لير"، ومسرحية "مكبيث"، وبطل ميللر التراجيدي، في مسرحية "موت بائع"، للتعرف على مدى التشابه والاختلاف بين كلتا الحالتين، حيث يتوصل البحث إلى نتيجة مهمة تتلخص في اعتبار نقاط التشابه بين الحالتين أكبر من نقاط الاختلاف، وأن بطل ميللر، من وجهة نظر النقد الحديث، الذي ينحدر من طبقة عامة الناس لا يقل وقعه التراجيدي في نفوس جمهور المستمعين، عن وقع البطل التراجيدي التقليدي ومكانته في مسرحيات شكسبير، أو حتى في المسرح الإغريقي.